Samba’a Naseha: Demo Masak Nugget Morfish dari Pangan Lokal Tinggi Protein - Ningsih, Lusi Novy Mery; Aulya, Marsya; Kariani, Ni Ketut; Yoduke, Fandy; Ikhwanudin, Ikhwanudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
Stunting remains a major public health issue in Indonesia, particularly in Donggala Regency, Central Sulawesi, with a prevalence of 34.1% in 2023. The contributing factors include limited access to health services, low socioeconomic conditions, and lack of parental knowledge regarding balanced nutrition. This community service activity aimed to improve public knowledge through a cooking demonstration using local food resources, featuring morfish nuggets made from yellowtail fish and moringa leaves, which are rich in protein and micronutrients. The method consisted of preparation, recipe trials, obtaining permissions, coordination with the community, and a cooking demonstration involving local mothers in Ganti Village, Donggala. The results indicated active participation of 12 mothers who directly engaged in cooking, learned about nutritional content, and practiced processing local food into healthy snacks. This activity successfully raised community awareness about the importance of balanced nutrition and provided a practical solution for stunting prevention using local food resources. In conclusion, the “Samba’a Naseha” cooking demonstration with morfish nuggets proved effective as a nutrition education medium, with potential to improve household dietary practices and support efforts to reduce stunting rates in endemic areas.